Characteristics of Rainfall in Dry and Wet Seasons in Iraq - Maisara Adnan Abdul Rahman (College of Education for Women, 2022)
This research aims at making a comparative survey between the dry season in (2017-2018) and the wet season (2018-2019) in Iraq concerning the variation of rainfall and pressure systems responsible for such a difference. In this paper, seven climatological stations have been selected: Mosul, Kirkuk, Khanaqin, Baghdad, Rutba, Diwaniyah and Basra. Results have shown that the first category of rainfall of the two seasons has recorded a higher number of rainy days in comparison with the second and third categories with a total of 274 day in a dry season and 403 day of a wet season. Further, the total amount of the annual continuous rain is higher than the total of thunderstorms in a dry season as well as in the majority of wet season stations except in Khanaqin, Baghdad. As for the highest daily precipitation, Kirkuk station has recorded 102.9 mm in a dry season, whereas Mosul station has recorded 308.2 in the wet season. It further occupied the highest monthly precipitation; it reached 291 mm in a dry season and 884.3 in a wet season. The study have found that El Nino phenomenon, which represents the negative values, has occurred during December and February while La Nina, which represents the positive values, has occurred during the rest of the year in the dry season. On the other hand, in wet seasons, the negative values (El Nino) continued for seven months while the positive ones (La Nina) continued for two months. Findings of surficial maps analysis have revealed that the highest overall frequencies and continuation have been for the Sudanese depression individually or jointly with the three categories of the dry season. Cold anticyclones and the Sudanese depression (individually or jointly) have recorded the highest frequencies, and continuation for the first category and the latter depression for the second and third categories of the wet season.